Cold-formed steel section building design - ANIL, KUMAR JELLA; MAHESH, YADAV ADLA (The journal of contemporary issues in business and government, 2020)
A relatively recent idea in India, cold formed steel sections are widely employed in industrial and non-industrial projects across the globe. In the 1990s, when the Indian economy opened up and a number of multi-nationals built up green-field projects, these ideas were brought to the Indian market. Local marketing agents and licenced builders have helped Global Cold formed steel create a footprint in India. There is no need to worry about compatibility issues since the whole building package is provided by a single vendor. There are several advantages to using the Cold formed construction technology, such as this: Because only bolted connections are employed, a structure may be dismantled, stored, or relocated to a new place and reassembled when no longer required. The stiff structure is sturdy despite the lack of field riveting or welding. The project may be completed in a shorter amount of time thanks to the use of a Cold formed system. In this study, an in-depth investigation of a cold-formed industrial building is conducted. Parametric investigations are taken into consideration as well. Hot Roll steel Industrial building and Cold formed Industrial building have been compared and a conclusion produced.